ANALISIS PENDAPATAN DAN EFISIENSI PEMASARAN BUAH NAGA MERAH DI DESA KOLOBOLON KABUPATEN ROTE NDAO - Windy Kos; Charles Kapioru; Siska Elvani (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Red dragon fruit is a horticultural commodity with considerable economic value and potential to improve farmers’ income in dry-climate regions. This study aims to analyze farm income and the marketing efficiency of red dragon fruit in Kolobolon Village, Lobalain District, Rote Ndao Regency. The study employed a quantitative descriptive approach. Respondents were selected using the census method, involving 22 red dragon fruit farmers and 10 marketing actors engaged in product distribution. Data were collected through observation, structured interviews, and documentation. Data analysis included production costs, revenue, farm income, marketing channels, marketing margins, farmer’s share, and marketing efficiency. The results show that red dragon fruit farming generates positive returns for farmers. Total revenue received by all farmers reached IDR 554,000,000, with an average revenue of IDR 25,181,818 per farmer, while total production costs amounted to IDR 82,905,000. Red dragon fruit is marketed through direct channels from farmers to consumers and indirect channels involving marketing intermediaries. Shorter marketing channels generate lower marketing margins and provide farmers with a higher share of the consumer price. These findings indicate that shortening the marketing chain can improve distribution efficiency and farmers’ income. Strengthening direct marketing, farmer institutions, and access to broader markets is necessary to improve farmers’ bargaining position and support the sustainability of red dragon fruit farming.